PENGARUH PERSEPSI KEGUNAAN DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP SIKAP PERILAKU PENGGUNA APLIKASI E-WALLET OVO - Octavia Dwipayanti, Riska; Khabibah, Umi (Cahaya Ilmu Bangsa, 2025)
OVO is a digital wallet application launched by PT Visionet Data Internasional. TAM (Technology Acceptance Model) is a technique for evaluating a technology's usability and advantages. The study sought to determine the impact of perceived utility and perceived simplicity of use on attitude behavior toward e-wallet OVO apps (study on Business Administration students at State Polytechnic of Malang). The study was explanatory, with two independent variables: perceived utility and perceived ease of use, and one dependent variable: attitude behavior. The study employed purposive sampling to get 49 responses. They used the users' e-wallet OVO application as an example. The data were then examined using multiple linear regression. Multiple linear regression revealed a substantial influence of advertising and brand image on purchasing choices of 50.5%. It was proved from Fvalue> Ftable (25,491 > 3,20) with a significant level of 0.000, which is less than 0.05. The study's findings supported the premise that perceived utility and perceived simplicity of use influence attitude behavior when using e-wallet OVO apps. This study concluded that OVO should be constant in sustaining quality. In the future, the corporation is anticipated to provide a simpler interface to attract more customers.